Proceedings of International Conference on Technology and Instrumentation in Particle Physics 2017 Volume 1 (Springer Proceedings in Physics,, 2018)
These two volumes present the proceedings of the International Conference on Technology and Instrumentation in Particle Physics 2017 (TIPP2017), which was held in Beijing, China from 22 to 26 May 2017. Gathering selected articles on the basis of their quality and originality, it highlights the latest developments and research trends in detectors and instrumentation for all branches of particle physics, particle astrophysics and closely related fields. This is the first volume, and focuses on the main themes Gaseous detectors, Semiconductor detectors, Experimental detector systems, Calorimeters, Particle identification, Photon detectors, Dark Matter Detectors and Neutrino Detectors. The TIPP2017 is the fourth in a series of international conferences on detectors and instrumentation, held under the auspices of the International Union of Pure and Applied Physics (IUPAP). The event brings together experts from the scientific and industrial communities to discuss their current efforts and plan for the future. The conference's aim is to provide a stimulating atmosphere for scientists and engineers from around the world.